2017
DOI: 10.21608/ejbo.2017.1032.1091
|View full text |Cite
|
Sign up to set email alerts
|

Short Term Effect of He-Ne Laser on Jatropha curcas Leaf Development and Amino Acid Biosynthesis: More Insights in Developmental Genetics of Oil Producing Plants

Abstract: JATROPHA curcas is a promising plant for biodiesel production. One tentative way to increase oil production is using non traditional physical methods such as laser. It had been shown before that laser could enhance plant growth and development as general. In this study, the DNA was extracted from leaves of plants grown from seeds collected from different regions in Egypt and tested using PCR to confirm their homogenousity. Then, the fully expanded leaves of Jatropha (6-week-old plants) were exposed to a dose e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…The increase in the metabolic activity of seeds is due to the absorption of more energy from the environment [12]. As indicated by the results of Khalifa et al [18], the transformation of glutamate to proline may refer to the induction of proline biosynthesis in plants by increasing the thickness of the cell walls. Irradiation of seeds with laser light stimulates ATP production, and thus an increase in crops in the form of mass [17,35].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The increase in the metabolic activity of seeds is due to the absorption of more energy from the environment [12]. As indicated by the results of Khalifa et al [18], the transformation of glutamate to proline may refer to the induction of proline biosynthesis in plants by increasing the thickness of the cell walls. Irradiation of seeds with laser light stimulates ATP production, and thus an increase in crops in the form of mass [17,35].…”
Section: Discussionmentioning
confidence: 97%
“…Photosynthesis is directly related to the production of biomass and the crop, as it is the source of energy for carbon fixation [40][41][42]. The laser light influences the metabolic activity of chloroplasts, leading, for example, to an increase in protein content through increased amino acid assimilation and increased starch storage [18,38]. According to Perveen et al [38] and Chen et al [12], pre-sowing laser light treatment of seeds increases the chlorophyll concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, information regarding the myco ora on soybean seeds coupled with laser irradiation is scarce. Khalifa et al [2017], indicated that the transformation of glutamate to proline may refer to the induction of proline biosynthesis in plants by increasing the thickness of the cell walls. Irradiation of seeds with laser light stimulates ATP production, and thus an increase in crops in the form of mass [Wilczek et al, 2006].…”
Section: Introductionmentioning
confidence: 99%